Measuring the performance of nations at Beijing Summer Olympics using integer-valued DEA model - Jie, W.; Zhixiang, Z.; Liang, L. (Journal of Sports Economics, 2010)
A number of studies have used data envelopment analysis (DEA) to evaluate the performance of the countries in Olympic Games. While the fact that numbers of three kinds of medal must only take integer values is ignored. This study discusses, by means of integer-valued DEA model, the performance of each country at 2008 Beijing Summer Olympic Games. The model in the article considers two inputs (gross domestic product [GDP] per capita and population) and three outputs (number of gold, silver, and bronze medals won); the integrality constraints of three kinds of medal and the weight restrictions among three outputs are also included. The results for the 2008 Beijing Summer Olympic Games are analyzed, and integral output targets are also provided for poorly performing countries to use as benchmarks.